Meningkatkan Hasil Belajar Bolabasket Dengan Memodifikasi Ring Basket (Department of Physical Education, Sport, Health and Recreation, 2015)
The study was about a classroom action research. The object of the study was a basketball hoop modification game, while the subject of the study was the sixth-grade students of SD Negeri Rowocacing Kecamatan Kedungwuni Kabupaten Pekalongan.Instruments used to obtain the data were the test observations and the students’ performance during the test. The results of the study showed an improvement in student learning outcomes from pre-cycle to cycle 1 and cycle 2, both from the improvement of the average score and the minimum mastery score. The average score of pre-cycle was (72.96), the average score of cycle 1 was (75.72) and the average score of cycle 2 was (78.52) so that the improvement from pre-cycle to cycle 2 was (5.56). The improvement of movement ability of the basketball learning could be seen from the Minimum Mastery Criteria (75) or completed by (36%), after doing the action on cycle 1, there were 15 of 25 students completed the score (60%) and on cycle 2 there were 21 of 25 students completed the score or totally was (84%)..